Openness and continuous collaboration as the foundation for entrepreneurial discovery process in Finnish regions - Mona Roman; Timo Nyberg (Management dynamics in the knowledge economy, 2017)
Entrepreneurial discovery process (EDP) is a bottom-up process engaging regional actors from academic, business, government and civil society together to identify new market opportunities and overcome the potential barriers to innovation. While EDP forms the key principle behind the smart specialization policy of European Commission, its operationalization has remained a challenge. We adopted a grounded theory approach to explore the dynamics of EDP through a case study in Finnish regions. Our aim is to identify the key underlying factors of EDP. Based on the semistructured interviews with 10 Finnish regions during September 2016, we identified openness, engaging, focused networking and continuous collaboration as the key factors underlying EDP. Our findings contribute to the theoretical debate on what constitutes EDP in the context of smart specialization. We also provide examples for policymakers how to implement these factors based on our case study.
10.25019/MDKE/5.4.04; 10.25019/MDKE/5.4.04; 2819566-8; 2392-8042; Management dynamics in the knowledge economy; 823675920